The Use of Role Playing Methods in Learning to Increase Student Learning Motivation - Rusnawati; Jarir; Siti Jamiatussoleha (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Teaching and learning activities are interactions that have educational value. In it, there is an educational interaction between teachers and students, when teachers deliver lessons to students in class. The learning materials that teachers provide will provide less encouragement (motivation) to students if the delivery uses inappropriate strategies. The learning process in class seems too rigid and less enjoyable, this also makes the lesson less meaningful, because mastery of the amount of material does not necessarily guarantee understanding of the material they have mastered. Student motivation in learning is very important and is the basis for students to achieve the expected learning competencies. The research methodology used in this study is descriptive qualitative research using the library research method. With the Role Playing Method, students can play an absolute part in the development of social human life. Role playing is often intended as a form of activity where learners imagine themselves as if they were outside the classroom and play the role of others. So that students can directly feel the situation and conditions in their surroundings. So, the Role Playing method can increase student motivation and learning outcomes.